Remembering the Modoc War : Redemptive Violence and the Making of American Innocence - Cothran, Boyd (Book collections on Project MUSE., 2014)
On October 3, 1873, the U.S. Army hanged four Modoc headmen at Oregon's Fort Klamath. The condemned had supposedly murdered the only U.S. Army general to die during the Indian wars of the nineteenth century. Their much-anticipated execution marked the end of the Modoc War of 1872-73. But as Boyd Cothran demonstrates, the conflict's close marked the beginning of a new struggle over the memory of the war. Examining representations of the Modoc War in the context of rapidly expanding cultural and commercial marketplaces, Cothran shows how settlers created and sold narratives of the conflict that.